Correction of Class II Division 2 Malocclusion with Traumatic deep bite -Non-extraction Therapy (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
This case report describe the management of a 22 years old male patient having class II div 2 malocclusion with traumatic deep bite. Intraoral examination revealed that patient had lingually inclined maxillary central incisor, labially flared maxillary lateral incisors, exaggerated lower curve of spee, and moderate crowding in lower jaw. Patient also tend to exhibit deep mentolabial sulcus and unaesthetic smile. Anterior flat bite plane was treatment plan for improving deep bite and also Mandibular downward backward rotation and Camouflage nonextraction treatment was decided for this patient because presence of lower crowding which is easy to correction and flare lower incisor for improving overjet and interincisal angle.Ban J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.33-36